Scientific and Technological Research in the Journal of High Andean Research in its six years of experience - Escobar-Mamani, Fortunato (2019)
Some universities in Peru, including the University of the Altiplano of Puno Peru do not necessarily make visible and visible their research, which in some cases became part of the heritage collection without knowing its validity or academic and scientific contribution. This editorial intends to highlight its publications in which to make the last six years of the magazine of the High Andean Research Magazine related to Scientific and Technological Research. The approach systematizes and values the weaknesses and strengths of the scientific visibility of its publications. The results achieved, among others, such as indexing in SciElo Peru, critically show their weaknesses while tending to strengthen their strengths to continue improving the visibility achieved and to continue advancing in the light of the scientific production produced in the other scientific journals of greater impact, to provoke reactions and positions that contribute to the achievement of the 2030 Sustainable Development Goals promoted by the United Nations Organization.